New Forms to Settle Old Scores: Updating the Worker Centre Story in the United States - Fine, Janice (Relations industrielles / Industrial Relations, 2011)
Worker centres are community-based mediating institutions that organize, advocate and provide direct support to low-wage workers. Moving into the void left by the decline of labour unions, local political parties and other groups, these centres are addressing issues that low wage, largely immigrant workers face at the workplace. In 1992, there were five such organizations, but by 2003, there were at least 137 worker centres in the United States rooted in communities where immigrant populations had settled. I estimate there to be more than 200 worker centres in 2011. Worker centres attract labourers who are often the hardest-to-organize and, because the organizations are unencumbered by the Wagner Act and subsequent Taft Hartley amendments which stripped unions of some of their most potent tactics, they can sometimes act as “organizing laboratories” creating and testing new and innovative strategies. Centres have had some significant organizing and public policy successes and have placed labour standards enforcement on the public policy agenda at the state and national levels. During their formative years, these organizations displayed important strengths but also exhibited weaknesses that appeared to limit their ability to get to scale. Over the last five years, they have moved into a new phase of development. Centres have shown institutional resilience. Not only have new centres emerged, but there has been a growing trend toward federation in which strong individual centres have joined existing national networks or formed new ones which have in turn helped to establish new organizations or affiliate existing ones. While some early worker centres were rejectionist toward the mainstream labour movement, the over-arching trajectory has been in the opposite direction with worker centres seeking cooperation. In fact, there is a growing trend toward institutional partnerships with unions and government. Finally, centres and their national networks are playing strategic roles in broader movement building around immigrant rights, global justice and the right to organize.